Nursing the spirit care, public life, and the dignity of vulnerable strangers - Grant, Don 1945- (Columbia University Press, 2023)
Illness and death have always raised profound spiritual concerns. However, today most people experience suffering and treatment in hospitals and other impersonal, bureaucratic facilities whose employees are expected to follow scientific, rationalized norms of behavior. How do professional caregivers-the nurses and other workers who tend to patients-navigate between science and spirituality?Don Grant investigates the subtle ways that nurses at an academic medical center incorporate spirituality into their care work. Based on extensive fieldwork and an in-depth survey on spirituality, this book finds that many nurses see themselves as responsible for not only patients' physical health but also their spiritual well-being. They believe they are able to reconcile science and spirituality through storytelling and claim that they can provide more spiritual care than chaplains. However, nurses rarely talk about religion among themselves because they are concerned that their colleagues are uncomfortable discussing spirituality. Nevertheless, by seeking to honor patients' ultimate worth as human beings, many nurses are able to instantiate spiritual values of care.Grant interweaves his experiences as a hospital volunteer chaplain and a living liver-transplant donor with empirical analyses of nurses' spiritual work. Developing a new understanding of the social significance of religion, Nursing the Spirit recasts the intersection of science and spirituality by centering the perspectives of the people who provide care